Two-spinon and orbital excitations of the spin-Peierls system TiOCl - Glawion, Sebastian; Haverkort, Maurits W. (Physical review letters, 2011)
We combine high-resolution resonant inelastic x-ray scattering with cluster calculations utilizing a recently derived effective magnetic scattering operator to analyze the polarization, excitation energy, and momentum-dependent excitation spectrum of the low-dimensional quantum magnet TiOCl in the range expected for orbital and magnetic excitations (0-2.5 eV). Ti 3d orbital excitations yield complete information on the temperature-dependent crystal-field splitting. In the spin-Peierls phase we observe a dispersive two-spinon excitation and estimate the inter- and intradimer magnetic exchange coupling from a comparison to cluster calculations.